Shanghai : a novel - Kanon, Joseph (Scribner, 2024)
"Shanghai begins when Daniel Lohr, sensing the Nazis closing in on the Jews of Berlin, leaves his dying father and agrees to flee to Shanghai on an Italian passenger ship. His passage is dependent upon him agreeing to deliver a package to his shady uncle upon arrival. Aboard the ship he will meet a woman, Leah, also a Jew fleeing the Nazis. They conduct a passionate but brief shipboard affair and then the passenger ship arrives. Will Dan ever see her again? He is met by his uncle--who has changed his name--and soon Dan is plunged into his uncle's world, specifically a big new nightclub, the best and most glitzy in town. Within minutes, violence breaks out as someone tries to assassinate his uncle, and with that, Dan is drawn deep into the underworld that is wartime Shanghai"--